KEEFEKTIFAN PEMBIAYAAN DALAM LINGKUP PERBANKAN SYARIAH UNTUK MENINGKATKAN KESEJAHTERAAN DALAM PENGELOLAAN EKONOMI MENENGAH KEBAWAH - Andreanto Indra Pratama; Fauzatul Laily Nisa (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to assess the effectiveness of Islamic banking financing in improving the economic welfare of low- to middle-income communities. Using descriptive analysis methods and a quantitative approach, this research analyzes data from several Islamic banks in Indonesia. The findings of this study indicate that financing based on Sharia principles, such as murabaha, mudaraba, and musharaka, makes a significant contribution to increasing the income and welfare of financing recipients. Additionally, the study reveals that Islamic banking has great potential to empower small and medium enterprises (SMEs) through more flexible and justice-based financing schemes. The conclusion of this study emphasizes the importance of developing and enhancing access to Islamic financing to support inclusive and sustainable economic growth for low- to middle-income communities.